Pengaruh Musik Terhadap Respirasi Bayi Berat Lahir Rendah Selama Kangaroo Mother Care Di RSUD Aloei Saboe Kota Gorontalo - Nancy Olii (Poltekkes Kemenkes Padang, 2019)
Every year in the world an estimated 20 million babies are born with low birth weight, a burden on social and community health in developing countries. LBW has difficulty in adapting to extra-uterine life due to the immaturity of the body's organ systems such as the lungs, heart, kidneys, liver, and digestive system. Efforts to increase respiration in LBW need to be given management pharmacologically and non-pharmacologically in the form of music. The purpose of this study was to determine the effect of music on LBW infant respiration during KMC in Aloei Saboe District Hospital, Gorontalo City. This type of research uses a quasi-experimental method, a sample of 30 people. Data were analyzed by Univariate and Bivariate by Paired T-test. Results: Based on statistical calculations using paired t-test obtained p value = 0,000 where sig <0.05, so that Ho was rejected and Ha was accepted, meaning that there was a significant difference between before classical music intervention and after classical music intervention on BBRR infant respiration during KMC at Aloei Saboe District Hospital. Conclusion: There is a positive influence between classical music on LBW respiration during KMC at Aloei Saboe Regional Hospital, Gorontalo City. Suggestion: Classical music can be played to optimize LBW care during KMC at the NICU and as an alternative in improving physiological responses, especially respiration in LBW infants.